Detection of IgG antibodies to Neospora caninum and Toxoplasma gondii in dogs examined in a veterinary hospital from Brazil - Mineo, TWP; Silva, DAO; Costa, GHN; von Ancken, ACB; Kasper, L. H.; Souza, M. A.; Cabral, D. D.; Costa, A. J.; Mineo, JR (Elsevier B.V., 2001)
A total of 163 dogs with neuromuscular, respiratory and/or gastrointestinal disorders, was admitted at the Veterinary Hospital, Federal University of Uberlandia, Brazil, and submitted to serology for Toxoplasma gondii and Neospora caninum. Assays for T gondii included indirect haemagglutination (IHA), indirect fluorescent antibody (IFAT-Tg), immunoenzymatic (ELISA), and immunoblotting (IB-Tg). Assays for N, caninum included IFAT-Nc and immunoprecipitation (IP-Nc). Based on concordant results by three serological tests (IHA, IFAT-Tg and ELISA) for T gondii, and divergent results further confirmed by IB-Tg for reactivity to TgSAG1, the 163 sera were divided into two groups: 59 (36%) Tg-seropositive samples and 104 (64%) Tg-seronegative samples. Antibodies to Neospora were detected in 11 (6.7%) out of 163 analyzed dog sera, with 5 (3.1 %) samples reactive to both parasites (Tg+/Nc+), and 6 (3.7%) reactive only to Neospora (Tg-/Nc+). Antibodies only to T: gondii were found in 54 (33%) samples. Among the 11 Neospora-positive sera analyzed by IB-Tg, the five sera Tg+/Nc+ showed strong reactivity to Toxoplasma antigens, especially to TgSAG1 (p30). No reactivity was observed to TgSAG1 in the six samples Tg-/Nc+. By TP-Nc, two highly immunodominant antigens (29 and 35 kDa proteins) were recognized by all 11 IFAT-Nc positive sera. Our results suggest that the infection by N, caninum can be concomitantly present in dogs from this area, although less common, and therefore should be considered in the differential clinical diagnosis with T. gondii in dogs presenting neuromuscular, respiratory and/or gastrointestinal disorders. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Neospora caninum; Toxoplasma gondii; dog; IgG antibodies